2015
DOI: 10.1016/j.jvs.2015.04.434
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Endurant stent graft in patients with abdominal aortic aneurysms independent of their morphologic suitability for endovascular aneurysm repair based on instructions for use

Abstract: The performance of the Endurant stent graft during a period of 7 years under real-life conditions was good, with low incidence of reinterventions and endoleaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…Numerous studies have since shown excellent midterm outcomes and rates of technical success with the device. 2,3,13,14 The data presented in this article confirm the long-term safety and durability of the Endurant system out to 5 years. The observation of only a single rupture at 4 years (day 1212), freedom from open surgical conversion, and freedom from aneurysm-related death (99.2%) supports the excellent long-term durability of the Endurant stent graft.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Numerous studies have since shown excellent midterm outcomes and rates of technical success with the device. 2,3,13,14 The data presented in this article confirm the long-term safety and durability of the Endurant system out to 5 years. The observation of only a single rupture at 4 years (day 1212), freedom from open surgical conversion, and freedom from aneurysm-related death (99.2%) supports the excellent long-term durability of the Endurant stent graft.…”
Section: Discussionsupporting
confidence: 74%
“…Treating patients with adverse proximal aortic necks (<10 mm) has been reported with acceptable short-term results. 13,14 However, an increased rate of type I endoleaks and mid-to late-term endograft migration is expected. The mean neck length treated in the study was 26.5 6 12.1 mm and 15 patients (10%) had neck lengths of 10 to 14.9 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies focused on the feasibility and the outcomes of Endurant II (Medtronic) used off-label. These studies also reported a higher incidence of type Ia endoleak and iliac limb occlusion for off-label stent use compared with patients treated under IFU (13)(14)(15).…”
Section: • September-october 2016 • Diagnostic and Interventional Radmentioning
confidence: 86%
“…3,4,8 Other papers that studied both stent grafts showed similar freedom from secondary intervention rates. [9][10][11] On the other hand, comparisons of the Talent and Endurant showed that the performance of the latter appears to be better. 7,12 The results of the U.S. regulatory pivotal trials of the Endurant and Talent were compared, showing favorable outcomes for the Endurant.…”
Section: Discussionmentioning
confidence: 99%